The Influence of Liquidity, Profitability, Firm Size, Tangibility and Growth on Capital Structure - Tursina, Anisya Amalia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the effects of liquidity, profitability, firm size, tangibility, and growth on the capital structure of consumer goods and industrial sector companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2022. Using the Generalized Method of Moments (GMM) in Eviews 12SV, 45 companies were analyzed based on purposive sampling. Results show tangibility and liquidity negatively influence capital structure, as firms with higher tangible assets and liquidity prefer internal financing. Conversely, firm size, profitability, and growth positively impact capital structure, with larger, more profitable firms adopting higher leverage due to increased access to external funding. This highlights the dynamic interplay of financial factors in shaping corporate capital structures.